2022
DOI: 10.1002/nau.24880
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder medication prescription trends from 2014 to 2018

Abstract: Purpose A growing literature points to an association between overactive bladder (OAB) medications and dementia. Given differences in side effects for extended‐release (ER) and immediate‐release (IR) anticholinergic formulations and beta‐3 agonists, we examined prescription utilization patterns in a national dataset of older adults from 2014 to 2018. Methods We performed a retrospective study using the Medicare Part D Drug Spending Dashboard, a publicly available database that includes data from outpatient pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In line with previous studies, the proportion of anticholinergic urinary antispasmodics (oxybutynin and tolterodine) decreased [12,15,21], which is a welcome and expected finding, as newer and safer drugs have emerged [25]. Interestingly, a major increase was seen in the use of antihistamines on Duran's list in ≥ 75-year-old communitydwelling people.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous studies, the proportion of anticholinergic urinary antispasmodics (oxybutynin and tolterodine) decreased [12,15,21], which is a welcome and expected finding, as newer and safer drugs have emerged [25]. Interestingly, a major increase was seen in the use of antihistamines on Duran's list in ≥ 75-year-old communitydwelling people.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, Sripad et al reviewed the choice of drug preferences for prescription between 2014 and 2018 and reported an increase in mirabegron use (from 5.7% to 20.1%) for the symptomatic treatment of OAB. However, antimuscarinics still constituted a greater proportion of total prescriptions as found in the medical records 26 . In another study comparing primary care providers, UROs, OB/GYNs, and other specialties' prescription patterns for OAB showed that mirabegron preference increased during the period from 2013 to 2017, and UROs prescribed mirabegron more frequently compared to other specialties 27 …”
Section: Discussionmentioning
confidence: 98%
“…However, antimuscarinics still constituted a greater proportion of total prescriptions as found in the medical records. 26 In another study comparing primary care providers, UROs, OB/GYNs, and other specialties' prescription patterns for OAB showed that mirabegron preference increased during the period from 2013 to 2017, and UROs prescribed mirabegron more frequently compared to other specialties. 27 In the present study, the most preferred drug among antimuscarinics was solifenacin with a significantly higher rate by UROs versus OB/GYN (58.2% vs. 28.2%; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%